Burkholderia cepacia sepsis in a patient with Acute Pancreatitis: A Case Report from Nepal - Khadka, Bikash; Khanal, Kishor; Budhathoki, Samip; Ghimire, Anup; Regmi, Ashim (Bangladesh Critical Care Journal, 2022)
Burkholderiacepacia is a rarely diagnosed infection in Nepal. Most cases of B.cepaciaare reported from South East Asia. It can present with a wide spectrum of clinical manifestations ranging from pneumonia to septicemia. We present a case of a 29-year-old man who had acute pancreatitis and was admitted to the hospital due to sepsis. B.cepaciawas isolated from ascitic fluid and was successfully treated with intravenous antibiotics. Bangladesh Crit Care J September 2022; 10(2): 146-148